2021
DOI: 10.2147/idr.s325056
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Multiplex Quantitative PCR Assay for Detection of Helicobacter pylori and Mutations Conferring Resistance to Clarithromycin and Levofloxacin in Gastric Biopsy

Abstract: Aims and Objectives: More than half of the world's population is infected with Helicobacter pylori, which can cause chronic gastritis. WHO has regarded clarithromycinresistant H. pylori as a high priority pathogen. Hence, accurate diagnosis and detection of clarithromycin-and levofloxacin-resistant H. pylori strains is essential for proper management of infection. The objective of this study was to develop and optimize multiplex quantitative PCR assay for detection of mutations associated with clarithromycin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Some studies have compared the agreement between the culture and the qPCR. For example, Monno et al reported an 80.6% concordance between the qPCR and the E-test for detecting clarithromycin resistance in gastric biopsies, and Bimaeil et al reported a significant concordance between these methods (Kappa = 0.85) [ 43 , 44 ]. The Maastricht V/Florence consensus report has already recognized that detecting genes and mutations associated with antibiotic resistance using molecular technologies is a valuable tool for detecting gastric biopsy specimens directly [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have compared the agreement between the culture and the qPCR. For example, Monno et al reported an 80.6% concordance between the qPCR and the E-test for detecting clarithromycin resistance in gastric biopsies, and Bimaeil et al reported a significant concordance between these methods (Kappa = 0.85) [ 43 , 44 ]. The Maastricht V/Florence consensus report has already recognized that detecting genes and mutations associated with antibiotic resistance using molecular technologies is a valuable tool for detecting gastric biopsy specimens directly [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…When drug susceptibility testing in culture is unavailable owing to time constraints, real-time PCR, 65,66 multiplex PCR, 67,68 fluorescence in situ hybridization, 69 and PCR-restriction fragment length polymorphism (PCR-RFLP) using gastric biopsy samples, 70,71 or PCR using stool samples 72,73 can be used to evaluate drug resistance to specific antimicrobial agents. Clarithromycin exerts its antibacterial activity by binding to the peptidyl transferase region of the 23S rRNA of H. pylori.…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…137,138 At labs, and gene chip technology is emerging along with PCR technologies. [140][141][142] Compared with traditional PCR and its derivative techniques, there are multiple reaction regions on the gene chip, and oligonucleotide probes are arranged in the reaction regions to test the target genes associated with resistance to different drugs, which has significant value in the diagnosis of H. pylori infection and in detecting its antimicrobial sensitivity. 143 A study in 2020 reported that the sensitivity and specificity of gene chip detection in the diagnosis of H. pylori infection were 96.1% and 85.0%, respectively.…”
Section: Molecular Detectionmentioning
confidence: 99%